Modulation of host cell signaling pathways as a therapeutic approach in periodontal disease - de Souza, João Antonio Chaves [UNESP]; Rossa Junior, Carlos [UNESP]; Garlet, Gustavo Pompermaier; Nogueira, Andressa Vilas Boas [UNESP]; Cirelli, Joni Augusto [UNESP] (FapUNIFESP (SciELO), 2012)
Recently, new treatment approaches have been developed to target the host component of periodontal disease. This review aims at providing updated information on host-modulating therapies, focusing on treatment strategies for inhibiting signal transduction pathways involved in inflammation. Pharmacological inhibitors of MAPK, NFkB and JAK/ STAT pathways are being developed to manage rheumatoid arthritis, periodontal disease and other inflammatory diseases. Through these agents, inflammatory mediators can be inhibited at cell signaling level, interfering on transcription factors activation and inflammatory gene expression. Although these drugs offer great potential to modulate host response, their main limitations are lack of specificity and developments of side effects. After overcoming these limitations, adjunctive host modulating drugs will provide new therapeutic strategies for periodontal treatment.
Keywords: Janus kinases; Mitogen-activated protein kinases; NF-kappa B; Periodontitis; Signal transduction; STAT transcription factors